Analisis Perbandingan Tools Forensic Pada Aplikasi Facebook Messenger Menggunakan Metode National Institute of Standards Technology (NIST) - Mualfah, Desti; Israndi, Febri; Ramadhan, Rizdqi Akbar (Unversitas Muhammadiyah Riau, 2025)
Therapid development of digital technology has driven a significant increase in internet and social media use across all levels of society. This situation not only facilitates communication and information exchange but also opens up opportunities for various forms of cybercrime. One social media platform frequently exploited in cybercrime activities is Facebook, particularly through its instant messaging feature. Therefore, a systematic and standardized digital forensic investigation process is needed to accurately obtain and analyze digital evidence. This study aims to analyze the application of digital forensic stages using the National Institute of Standards and Technology (NIST) method on the Facebook social media platform. The research method used is acase study with a digital forensic approach based on the NIST framework, which includes the stages of collection, examination, analysis, and reporting. The process of acquiring and analyzing digital evidence was carried out on an Android-based smartphone device using two forensic tools, namely Magnet AXIOM and MOBILedit Forensic. The results of the study indicate that MOBILedit Forensic has better data acquisition capabilities, especially in extracting application artifacts and image data relevant to the case. Meanwhile, Magnet AXIOM demonstrates superiority in aspects of data analysis, result visualization, and integration with other forensic platforms. Based on the results of the comparison, MOBILedit Forensic is recommended as a more effective digital forensic tool for the investigation process on Android devices, especially in handling cybercrime cases involving social media applications.